Analysis of PM-bound polycyclic aromatic hydrocarbons exposure among motorcycle taxi drivers in six central provinces in Thailand in winter - Kamonwan Samana; Kimihito Ito; Orasa Suthienkul; Arroon Ketsakorn (PLoS ONE, 2025)
Motorcycle taxis are popular transportation in areas with heavy traffic in Thailand. In this study, we recruited motorcycle taxi drivers in six central provinces in Thailand between January and March 2023 and measured their particulate matter (PM) and PM-bound polycyclic aromatic hydrocarbon (PAH) exposures using personal air sampling. We found that the PM 10 and PM 2.5 concentrations measured by personal air sampling were independent of those monitored at air quality monitoring stations or by area air sampling devices. Among the six provinces, motorcycle taxi drivers in Pathum Thani were exposed to the highest mean concentration of PM 10 (224.9 µg/m 3 ), PM 2.5 (410.9 µg/m 3 ), PM 10− bound total PAH (38.4 ng/m 3 ), and PM 2.5 -bound total PAH (36.9 ng/m 3 ). Four workstations (PTT-1 to PTT-4) using 22 samples of PM₁₀ and 25 samples of PM₂.₅ personal air samplers showed unexpectedly higher PM₂.₅ than PM₁₀, likely due to route-specific environmental factors, as drivers follow variable routes determined by passenger destinations and daily demand. The incremental lifetime cancer risk of PM 10− bound PAH and PM 2.5 -bound PAH in Pathum Thani were 4.5 × 10 −8 and 7.8 × 10 −8 , respectively, which were acceptable levels. None of the individuals’ lung function parameters was significantly correlated with the individuals’ concentrations of PM 10 , PM 2.5 , PM 10− bound total PAH, or PM 2.5 -bound total PAH. However, province averages of PM 10 -bound total PAH exposure of motorcycle taxi drivers were positively correlated with the proportions of participants who answered symptoms of chronic bronchitis in the province. The causal relationship between motorcycle taxi drivers’ PM and PM-bound PAH exposure in Pathum Thani and their respiratory symptoms needs to be further investigated.